Taking a position by another body when issuing an administrative decision by a competent body (Discourse of Law and Administration, 2019)
Changes made in the Code of administrative proceedings by the act of April 7th, 2017 on amending the act – the Code of administrative proceedings and certain other acts by introducing Article 7b in Section 1 chapter 2 of CAP “General Principles” raised to the status of a general principle the obligation of cooperation of administration bodies in the situation of fulfilling the conditionsof this article. The regulations of the Code of administrative proceedings (CAP) referring to the institution of cooperation of administrative bodies may be divided into two groups: 1) cooperation of bodies of a procedural nature involving the institution of legal aid (Article 52 c.a.p.) as well as regulations referring to a request of a party to submit a document copy or excerpt by a public administration body if the party cannot obtain it, or a request to deliver an original document by the body if it is necessary to review it (Article 76a § 1 c.a.p.); 2) cooperation of bodies of a substantive and procedural nature involving the institution of taking a position by another body in administrative proceedings carried out by a competent body to resolve the case.
Keywords: taking a position by another body when issuing an administrative decision by a competent body; cooperation of public administration bodies